The efficacy and safety of acetazolamide in chronic mountain sickness: A systematic review and meta‐analysis of randomized controlled trials - Yaqin Wang; Zhengcai Han; Zhouzhou Feng (PLoS ONE, 2025)
Objective The impact of acetazolamide (ACZ) in chronic mountain sickness (CMS) has not been fully assessed. The purpose of this systematic review is to evaluate the effectiveness and safety of acetazolamide in the treatment of chronic mountain sickness. Research methods This systematic review and meta-analysis were conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The primary outcome measure was CMS clinical score. Secondary outcomes included CMS total score,hematocrit (HCT), Pondus Hydrogenii‌ (pH), arterial oxygen pressure (PaO2), arterial carbon dioxide pressure (PaCO2), bicarbonate concentration (HCO3), and adverse events. Results Five randomized controlled trials were included, comprising a total of 137 subjects, with 78 in the acetazolamide group and 59 in the control group.The CMS clinical score showed an MD of −0.31 (95% CI, −1.13 to −0.51, P = 0.46),the results indicated no statistical significance.But the CMS total score had an MD of −1.13 [95% CI, −2.03 to −0.23], P = 0.01, showing a significant difference.The HCT results showed an MD of −2.70 (95% CI, −4.58 to −0.82; P = 0.005), indicating a statistically significant reduction. The result of PaO2,PaCO2,pH and HCO3 are statistically significant. In terms of adverse events, increased diuresis and headache were not statistically significant. Paresthesia had a significant difference. Conclusion Based on the available evidence, we conclude that ACZ 250 mg is a safe, reliable, and low-cost treatment option for chronic mountain sickness. By reducing HCT, PaCO2, pH, and HCO3, and increasing PaO2, it improves respiratory and circulatory parameters in CMS patients and effectively treats CMS.